THE IMPLEMENTATION OF INDONESIA’S PUBLIC POLICY TO IMMIGRATION SELECTIVE POLICY BASED ON LAW NO. 6 OF 2011 - Muhammad Azzam Alfarizi (Jurnal Ilmiah Kajian Keimigrasian, 2018)
The inherent right of the individual is an affirmation that human beings must be treated properly and civilized and must be respected, as the sounding of the second precept is: "Just and Civilized Humanity". Human rights are manifestations of the third principle, namely: "Indonesian Unity". If all rights are fulfilled, reciprocally the unity and integrity will be created. Rights are also protected and upheld as is the agreement of the fourth precepts that reads: "Democracy Led by Wisdom in Consultation / Representation". Human Rights also recognizes the right of every person for the honor and protection of human dignity and dignity, which is in accordance with the fifth precepts which read: "Social Justice for All Indonesian People" PASTI Values ​​which are the core values ​​of the Ministry of Law and Human Rights which is an acronym of Professional, Accountable, Synergistic, Transparent and Innovative is an expression of the performance of the immigration apparatus in providing human rights based services. If these values ​​are in line with the values ​​contained in Pancasila, the criteria for evaluating human rights-based public services are based on the accessibility and availability of facilities; the availability of alert officers and compliance of officials, employees, and implementers of Service Standards for each service area will be easily achieved. It is fitting that immigration personnel in providing services must be in accordance with the principles of human rights-based services and in harmony with the Pancasila philosophy. This is as an endeavor in fulfilling service needs in accordance with the mandate of the 1945 Constitution, provisions of applicable laws and human rights principles for every citizen and population for services provided by the government in this case Immigration.